Palladium-catalyzed annulative π-extension of o-halobiphenyls with o-chloropyridinecarboxylic acids to access azatriphenylenes. Issue 44 (25th October 2022) - Cheng, Shu-Lin; Fan, Xin-Yue; Zhu, Ji-Fa; Wang, Bi-Qin; Shi, Yingbo; Feng, Chun; Xiang, Shi-Kai
Abstract : A palladium-catalyzed bay-region annulative π-extension reaction of o -halobiphenyls with o -chloropyridinecarboxylic acids was developed. A variety of azatriphenylene derivatives could be synthesized by this approach. Abstract : A palladium-catalyzed bay-region annulative π-extension reaction of o -halobiphenyls with o -chloropyridinecarboxylic acids was developed. The reaction was carried out with a 1 : 1 ratio of substrates. A variety of azatriphenylene derivatives could be synthesized by this approach. This transformation could be applied to the synthesis of ionic liquid-crystalline molecules.